Inter-Collateral Diabetic Retinopathy Extraction and Evaluation Using Trained Datasets of Multiple Feature Set - E. Logashanmugam, K. T. Ilayarajaa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Diabetic Retinopathy (DR) is caused due to un-mounted diabetic comorbidities. The patients suffer complete vision blindness if untreated or diagnosed on later stage. In this article, we propose a novel approach for early detection and prediction using trained datasets of multiple features. The process expansion is resultant of multiple stage attribute extraction via a series of inter-collateral parameters of diabetics. Typically, the proposed technique is designed and developed on a multi-value and multi-dimension datasets such as comorbidities history of patient encountered during diabetics. The proposed technique uses collateral attributes in evaluating retinopathy status and thereby validates the extracted DR under threshold value comparisons. The results are computed using HADOOP framework for recursive pattern and feature evaluation. The trial is processed on UCL digital library datasets with estimated performance of 98.7% with extraction and 92.34% with value True-Positive (TP) prediction.